FLEXIBLE PAVEMENT REMAINING LIFE DUE TO ELASTIC MODULUS DECREASE BASED ON THE BINA MARGA 2017 METHOD AND THE ASPHALT INSTITUTE METHOD - Harnaeni, Senja Rum; Sunarjono, Sri; Maghfirona, Alfia; Larasati, Vela Putri; Tanoedji, Zulfa Nadhira; Ibrahim, Hendy Ilfat; Ayob, Afizah (Journal of Applied Engineering Science, 2025)
This research compares the remaining life of flexible pavement that experiences a decrease in elastic modulus due to road usage, utilizing The Bina Marga 2017 Method and The Asphalt Institute Method. The study begins with a structural evaluation of the pavement, field core sampling, and laboratory modulus testing. Variations in the asphalt mixture's elastic modulus are analyzed at 100%, 80%, and 60% of its original value for each layer. Using KENPAVE software, simulations determine the horizontal tensile strain on the bottom of asphalt layer to predict fatigue life and the vertical compressive strain on the top of subgrade for rutting life. The study also includes a traffic survey to assess traffic load, and remaining life calculations provide longevity predictions across both methods. The results indicate that a decrease in the elastic modulus value of the flexible pavement layer leads to a reduction in both fatigue life and rutting life, ultimately affecting the overall remaining life of the pavement. Notably, the remaining life assessments for fatigue and rutting calculated using The Bina Marga 2017 Method yield greater values than those determined by The Asphalt Institute Method. Therefore, it is recommended to utilize The Asphalt Institute Method for planning purposes, as it provides more conservative results, ensuring safer planning compared to The Bina Marga 2017 Method.
Keywords: fatigue life, rutting life, remaining life, elastic